Susceptibility to dengue hemorrhagic fever in vietnam: evidence of an association with variation in the vitamin d receptor and Fc gamma receptor IIa genes. - Loke, H; Bethell, D; Phuong, C; Day, N; White, N; Farrar, J; Hill, A (2002)
Dengue is an increasingly important cause of morbidity and mortality in the tropics, with more than a billion people at risk each year. Immunologic enhancement is thought to contribute to disease pathogenesis. Only a very small proportion of infected individuals develop life-threatening dengue hemorrhagic fever (DHF). In a large case-control study with 400 DHF patients and 300 matched controls, we have assessed five polymorphic non-HLA host genetic factors that might influence susceptibility to DHF. The less frequent t allele of a variant at position 352 of the vitamin D receptor (VDR) gene was associated with resistance to severe dengue (P = 0.03). Homozygotes for the arginine variant at position 131 of the Fc gammaRIIA gene, who have less capacity to opsonize IgG2 antibodies, may also be protected from DHF (one-tailed P = 0.03). No associations were found with polymorphisms in the mannose binding lectin, interleukin-1 (IL-4), and IL-1 receptor antagonist genes. Further studies to confirm these associations are warranted.